2002
DOI: 10.1083/jcb.200204059
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling to identify genes involved in peroxisome assembly and function

Abstract: Yeast cells were induced to proliferate peroxisomes, and microarray transcriptional profiling was used to identify PEX genes encoding peroxins involved in peroxisome assembly and genes involved in peroxisome function. Clustering algorithms identified 224 genes with expression profiles similar to those of genes encoding peroxisomal proteins and genes involved in peroxisome biogenesis. Several previously uncharacterized genes were identified, two of which, YPL112c and YOR084w, encode proteins of the peroxisomal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
236
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 173 publications
(256 citation statements)
references
References 54 publications
20
236
0
Order By: Relevance
“…Although small punctate structures were observed in cells expressing Gpd1p-GFP (Ser to Ala), our data suggest that the import of Gpd1p into peroxisomes is increased by phosphorylation adjacent to its PTS2 and that the cell exploits this post-translational modification to control the localization of Gpd1p. To confirm and extend the confocal data, subcellular fractions from cells expressing Gpd1p-GFP, Gpd1p-GFP (Ser to Ala), or Gpd1p-GFP (Ser to Asp) were prepared by differential centrifugation (24,36). Consistent with the microscopy data, Western blot analysis showed that Gpd1p-GFP (Ser to Ala) is present in reduced amounts in the 20KgP fraction compared with Gpd1p-GFP or Gpd1p-GFP (Ser to Asp) (Fig.…”
Section: Gpd1pmentioning
confidence: 57%
See 1 more Smart Citation
“…Although small punctate structures were observed in cells expressing Gpd1p-GFP (Ser to Ala), our data suggest that the import of Gpd1p into peroxisomes is increased by phosphorylation adjacent to its PTS2 and that the cell exploits this post-translational modification to control the localization of Gpd1p. To confirm and extend the confocal data, subcellular fractions from cells expressing Gpd1p-GFP, Gpd1p-GFP (Ser to Ala), or Gpd1p-GFP (Ser to Asp) were prepared by differential centrifugation (24,36). Consistent with the microscopy data, Western blot analysis showed that Gpd1p-GFP (Ser to Ala) is present in reduced amounts in the 20KgP fraction compared with Gpd1p-GFP or Gpd1p-GFP (Ser to Asp) (Fig.…”
Section: Gpd1pmentioning
confidence: 57%
“…Subcellular Fractionation-Subcellular fractionation was performed as described previously (24,36). Briefly, yeast cells were grown to mid-exponential growth phase (A 600 ϳ1) in SMLeu.…”
Section: Methodsmentioning
confidence: 99%
“…The microarray data extend to at least 12, the number of genes encoding peroxisomal proteins that are dependent on ADR1 for expression in the absence of oleate (Table III). Many of the ADR1-dependent genes scored high in a genomic profile of genes involved in peroxisome assembly or function (39) and were also identified in a search for oleate-inducible, OAF1-PIP2-dependent genes (40,41). In addition to ␤-oxidation, uptake of fatty acyl-CoA by peroxisomes appears to be ADR1-dependent.…”
Section: Resultsmentioning
confidence: 99%
“…(20), and pRS406 (21) have been described previously. pmRFP-SKL was constructed by replacing the gene for red fluorescent protein in the plasmid pDsRed-PTS1 (22) with the gene encoding monomeric red fluorescent protein (mRFP) (23). pGFPϩ/HIS5 and pmRFP/HIS5 were constructed by replacing the gene for GFP in pGFP/HIS5 (24) by the genes encoding GFPϩ (25) and mRFP, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Analytical Procedures-Subcellular fractionation was performed as described previously (22). Whole cell lysates were prepared as described previously (27).…”
Section: Aa-gfp (His5)/pex3::gal1pex3-mrfp (His5)mentioning
confidence: 99%